PENGARUH DISIPLIN KERJA DAN KOMITMEN TERHADAP PENINGKATAN KINERJA GURU SMA NEGERI SE KABUPATEN ASAHAN - Siahaan, Albertus (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The school's vision is to excel in achievement, have a science and technology perspective based on IMTAQ and be based on the environment, while the school's mission is to foster a pious personality towards God Almighty, organize effective learning to optimize the potential of environmentally aware students, develop active, creative, and innovative attitudes, add appreciation to religious teachings that are environmentally aware, create a clean, healthy and shady environment, care about environmental functions. As a mentor, teachers must guide students in a direction that is in accordance with educational goals. The formulation of the problem in this study is 1) How much influence does work discipline have on the performance of SMA Negeri teachers in Asahan Regency, 2) How much influence does commitment have on the performance of SMA Negeri teachers in Asahan Regency, 3) How much influence does work discipline and commitment simultaneously have on the performance of SMA Negeri teachers in Asahan Regency. The objectives of this study are 1) The influence of work discipline on the performance of SMA Negeri teachers in Asahan Regency, 2) The influence of commitment on the performance of SMA Negeri teachers in Asahan Regency, 3) The influence of work discipline and commitment simultaneously on the performance of SMA Negeri teachers in Asahan Regency. The population of this study was 562 teachers at state high schools in Asahan Regency. Because the number of teachers as a population is more than 100, a sample of 15% was taken so that the sample totaled 84 teachers. The data analysis technique used was influence analysis using the SPSS version 20 program. The tests used were the t-test, F-test and coefficient of determination. The results of the study showed that partially the work discipline variable influenced teacher performance at state high schools in Asahan Regency, where there was an influence of 56.40%, meaning that the better the work discipline, the higher the teacher's performance. Partially, the commitment variable influenced teacher performance at state high schools in Asahan Regency, where there was an influence of 62.60%, meaning that the better the commitment, the higher the teacher's performance. Simultaneously, the work discipline and commitment variables influenced the performance of state high school teachers in Asahan Regency, where 80.20% of the variation in teacher performance could be explained by work discipline and commitment simultaneously, while the remaining 19.80% was explained by other factors, such as motivation and organizational culture variables. Keywords: Work Discipline, Commitment, Teacher Performance Abstrak: Visi sekolah adalah unggul dalam prestasi, berwawasan IPTEK berdasarkan IMTAQ dan berbasis lingkungan hidup, sedangkan misi sekolah adalah menumbuhkan pribadi bertakwa terhadap Tuhan Yang Maha Esa, menyelenggarakan pembelajaran yang efektif untuk mengoptimalkan potensi siswa berwawasan lingkungan, mengembangkan sikap aktif, kreatif, dan inovatif, menambahkan penghayatan terhadap ajaran agama yang berwawasan lingkungan hidup, menciptakan lingkungan yang bersih, sehat dan rindang, peduli terhadap fungsi lingkungan. Sebagai pembimbing, guru harus menuntun anak didik ke arah yang sesuai dengan tujuan pendidikan.  Rumusan masalah dalam penelitian ini adalah 1) Seberapa besar pengaruh disiplin kerja terhadap kinerja guru SMA Negeri Se Kabupaten Asahan, 2) Seberapa besar pengaruh komitmen terhadap kinerja guru SMA Negeri Se Kabupaten Asahan, 3) Seberapa besar pengaruh disiplin kerja dan komitmen secara simultan terhadap kinerja guru guru SMA Negeri Se Kabupaten Asahan. Tujuan penelitian ini adalah 1) Pengaruh disiplin kerja terhadap kinerja guru SMA Negeri Se Kabupaten Asahan, 2) Pengaruh komitmen terhadap kinerja guru SMA Negeri Se Kabupaten Asahan, 3) Pengaruh disiplin kerja dan komitmen secara simultan terhadap kinerja guru guru SMA Negeri Se Kabupaten Asahan. Populasi penelitian ini guru sma Negeri Se Kabupaten Asahan sebanyak 562 orang guru. Karena jumlah guru sebagai populasi lebih dari 100 maka diambil sampel 15 % sehingga sampel berjumlah 84 guru. Teknik analisis data yang digunakan adalah analisis pengaruh dengan menggunakan program SPSS versi 20. Uji yang digunakan adalah uji t, uji F dan koefisien determinasi. Hasil penelitian menunjukkan bahwa secara parsial variabel disiplin kerja berpengaruh terhadap kinerja guru pada SMA Negeri Se Kabupaten Asahan, dimana terdapat pengaruh sebesar 56,40 % artinya semakin baik disiplin kerja maka kinerja guru juga akan semakin tinggi. Secara parsial variabel komitmen berpengaruh terhadap kinerja guru pada SMA Negeri Se Kabupaten Asahan, dimana terdapat pengaruh sebesar 62,60 % artinya semakin baik komitmen maka kinerja guru juga akan semakin tinggi. Secara simultan variabel disiplin kerja dan komitmen mampunyai pengaruh terhadap kinerja guru SMA Negeri Se Kabupaten Asahan, dimana sebesar 80,20 % variasi kinerja guru dapat dijelaskan oleh disiplin kerja dan komitmen secara serempak, sedangkan sisanya 19,80 % lagi dijelaskan oleh faktor lain, yaitu seperti variabel motivasi dan budaya organisasi. Kata kunci: Disiplin Kerja, Komitmen, Kinerja Guru